Prevalence and risk factors on work-related musculoskeletal discomforts among nurses in Hospital Universiti Sains Malaysia - Deruis, Nurfadzlina (Universiti Sains Malaysia, 2016)
A cross sectional study was conducted to determine the prevalence and risk factors (individuals, work characteristic and psychosocial) to Work-Related Musculoskeletal Discomforts (WRMDs) among nurses in USM hospital. Questionnaires were distributed among the respondents to seek the information on variables of study. This study found that the predominant body regions on WRMDs within 12 months were ankles/feet (35.6%), neck (33.3%) and lower back (31.3%). Upper back, shoulders, knees, wrists/hands, and hips/thighs were the less reported pain by nurses with 28.9%, 22.2%, 20%, 17.7% and 13.3% respectively. Ankles/feet pain was the commonest complaint among the respondents. Shoulder pain was significantly associated with gender (%2 = 9.129, p = 0.010) and heavy lifting techniques (x2 = 6.544, p = 0.011). Housework routine was significantly associated with neck pain (x2 = 4.486, p = 0.041), wrists/hand pain (x2 = 10.317, p = 0.016) and upper back pain (x2 = 5.152, p = 0.023). Lower back was significantly associated with work psychosocial involvement (x2 = 4.394, p = 0.036). Neck pain was significantly associated with marital status (x2 = 6.544, p = 0.011) and having children (x2 = 4.549, p = 0.033). Upperback pain was significantly associated with having children (x2 = 4.549, p = 0.033). In addition, changing position of patient in bed, carrying the patient to and from the toilet and repetitive work posture were the work characteristics that contributed to knee pain (x2 = 8.372, p = 0.004). In contusion, the prevalence of WRMDs among the nurses was more than 50% and was comparable to other studies. Thus, greater actions should be adopted by the administration and individual in order to control more severe WRMDs in nursing professionals.